A Pareto-Based Particle Swarm Optimization Algorithm for Multi-Objective Location Routing Problem - Liu, Jie; Kachitvichyanukul, Voratas (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
This paper deals with multi-objective location routing problem (MOLRP). The two conflicting objectives considered are the minimization of total cost and maximization of total customer demand served. The MOPSO algorithm by Nguyen and Kachitvichyanukul (2010) is applied to solve this problem by searching for the Pareto front. A specific solution representation and two different decoding are designed for MOLRP problems. The test problem instances used to test the algorithm are modified from previously published test problem instances for single objective LRP. The experimental results demonstrated that the proposed algorithm can effectively provide nice Pareto front for most test problem instances by both decoding methods but with different solution quality.